PENDEKATAN SOSIOLOGI HUKUM DALAM MEMAHAMI KONFLIK PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Aldi Wiratama; Ajie Haikal; Zainudin Hasan (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indeed, regulation has become a hot topic of discussion in recent years. Laws and regulations, which are essentially a collection of regulatory systems designed to maintain a regulated society, frequently result in conflicts—internal conflicts between regulations and external conflicts involving community members and government agencies. Because society is at the beginning and end of a regulation, the study of legal science from the perspective of sociological jurisprudence is a scientific tool that makes sense for analyzing the phenomenon of legal problems in Indonesia. The findings demonstrate that regulatory conflicts arise as a result of the fact that, in practice, procedural and substantive due process of law are frequently ignored when laws and regulations are drafted. One of the main points is that as much public input as possible is required when drafting regulations. Due to a mismatch between the regulations' substance and the community's conditions and requirements, numerous regulations frequently result in conflicts.